2019
DOI: 10.1002/aenm.201803583
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Ultrathin Co3O4 Nanosheet Supported PdO/CeO2 Catalysts for Methane Combustion

Abstract: As one of the most important noble metals, Pd species including Pd 0 and PdO x based catalysts have exhibited excellent catalytic activity toward methane combustion at relatively low temperatures. [2,3] During manufacturing applications the active Pd species were usually loaded on metal oxides (MO x ) supports via the traditional deposition precipitation [4,5] or impregnation [6,7] methods in which good Pd dispersion could result in ideal initial catalytic activity. However, these strategies brought an obvious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 54 publications
(77 reference statements)
1
20
0
Order By: Relevance
“…The results well correlate with the previous reports. [ 38,40,41 ] Figure 1e shows multiple peaks with spin–orbit doublets corresponding to Ni 2p 3/2 and Ni 2p 1/2 components in Ni 2p. The binding energy peaks at 854.29 and 871.88 eV attributes to the Ni 2+ state and 856.00 and 874.33 eV attributes to Ni 3+ state in Ni 2p doublets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results well correlate with the previous reports. [ 38,40,41 ] Figure 1e shows multiple peaks with spin–orbit doublets corresponding to Ni 2p 3/2 and Ni 2p 1/2 components in Ni 2p. The binding energy peaks at 854.29 and 871.88 eV attributes to the Ni 2+ state and 856.00 and 874.33 eV attributes to Ni 3+ state in Ni 2p doublets.…”
Section: Resultsmentioning
confidence: 99%
“…The results well correlate with the previous reports. [38,40,41] Figure 1e shows multiple peaks with spin-orbit doublets corresponding to Ni 2p 3 [42,43] XPS spectrum of O 1s shows three distinct deconvoluted peaks as shown in Figure 1f. The binding energy peak at 529.73 eV corresponds to the bonding between metal-oxygen (CoO or NiO in the present case), whereas the peaks centered at 530.97 and 532.34 eV can correspond to the oxygen molecules chemisorbed on the sample as surface hydroxyls.…”
Section: Raman Spectra Of Both Co 3 O 4 @Nf and 5 Nm Nio/co 3 O 4 @ Nmentioning
confidence: 96%
“…Li et al. reported that the combination of Pd species and hybrid oxide centers in the Co 3 O 4 −CeO 2 interface affords a positive reaction pathway for the catalytic lean methane combustion [12] . Moreover, the Pt‐SAs stabilized at the CeO x −TiO 2 hybrid interfaces was reported to be more active toward CO oxidation via activating the interface‐mediated MvK mechanism and facilitating its catalytic performance against CO‐poisoning [13] .…”
Section: Methodsmentioning
confidence: 99%
“…It is widely recognized that the formation of reduced Ce 3+ species is associated with the generation of oxygen defect sites due to a charge compensation [27] . According to the previous literatures, [12,28] the surface Ce 3+ concentration is identified by the total peak area of S1 (v ′ + u ′ ), and the amount of Ce 4+ is calculated by S2 (v 0 +v ′′ +v ′′′ +u 0 +u ′′ +u ′′′ ). As showed in Ce 3d XPS spectra (Figure 6), the ratio of Ce 3+ can be determined by the relation of S1/(S1+S2).…”
Section: Methodsmentioning
confidence: 99%
“…However, the inherently high electronic resistance and low surface area of Co 3 O 4 retard its practical application [12]. Generally, the electrocatalytic properties of materials are strongly dependent on their morphology and microstructures, which creates substantial differences in the surface area, particle size, pore structure, mass transport, and electron transfer efficiency, which in turn influence their electrochemical sensing performance [13]. Therefore, the morphology and nanostructure control of Co 3 O 4 are of vital importance to improve the electrochemical reactivity [6].…”
Section: Introductionmentioning
confidence: 99%